Influence of Judo Experience on Neuroelectric Activity During a Selective Attention Task - Faro, Heloiana Karoliny Campos; Machado, Daniel Gomes da Silva; Bortolotti, Henrique; do Nascimento, Paulo Henrique Duarte; Moioli, Renan Cipriano; Elsangedy, Hassan Mohamed; Fontes, Eduardo Bodnariuc (Frontiers in Psychology, 2020)
Objective We compared the cognitive performance and neuroelectric responses during a selective attentional task in judo athletes with different levels of expertise. Methods Judo black and white belt athletes performed both general and specific fitness tests while simultaneously completing a Stroop color-word test recorded by 64 electroencephalogram channels. Results Cognitive behavioral performance and event-related spectral perturbation (ERSP) present no differences between groups. However, the topographic analysis found different neural source patterns in each group. Judo black belts compared to judo white belts presented a greater peak amplitude of P300 in the middle frontal gyrus and of N200 in the cuneus, but slower latency of P300 in the precuneus. Conclusion Despite no difference in cognitive behavioral performance, judo expertise causes a difference in the allocation of attentional and conflict detection neural resources.